CRIME PREVENTION THROUGH DIGITALIZATION - Dimovski, Darko T (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The usual prevention measures do not give the expected results. Therefore, the author starts from the fact that we should think about the possibilities of using the achievements of the modern world in crime prevention. One of those possibilities is digitalization. The author believes that there are four directions in which it is possible to observe the impact of digitalization on crime prevention: 1. digitalization of currencies, 2. digitalization of identities and signatures, 3. use of smart devices and 4. use of mobile applications. In the continuation of the paper, the author explains each of the mentioned directions, stating the ways of crime prevention.